Effect of reciprocal teaching strategy on physics student’s academic self-concept - Nofouz Mafarja; Hutkemri Zulnaidi; Hidayah Mohd Fadzil (International Journal of Evaluation and Research in Education (IJERE), 2023)
This research determined the impact of reciprocal teaching strategies on students’ academic self-concepts in physics. Reciprocal teaching is a collaborative strategy in the form of dialogue between teachers and students about a text containing eight techniques. Provide predictions, question generation, clarifications, connections, visualizations, summaries, calculations, and feedback to measure students’ academic self-understanding in physics. Two groups were experimental groups (n=60) and learned physics through an interactive teaching strategy. The other group, a control group (n=60), studied physics in a traditional way, judged the effectiveness of each other’s teachings, and compared the control group with a controlled trial. Results indicated that mutual education was more effective than traditional approaches in improving students’ academic self-concept. The results showed that mutual teaching is a more effective strategy than traditional methods to improve students’ academic self-concept. There was a significant difference between the experimental group and the control group. In this study, we proposed using the reciprocal teaching strategy in secondary school physics classes to improve students’ physics learning. Teachers should also receive maintenance and maintenance training to integrate reciprocal teaching into the classroom environment.